Exploring the Potential of β-Catenin O-GlcNAcylation by Using Fluorescence-Based Engineering and Imaging - Angelina Kasprowicz; Corentin Spriet; Christine Terryn; Vincent Rigolot; Stephan Hardiville; Matthew G. Alteen; Tony Lefebvre; Christophe Biot (Molecules, 2020)
Monitoring glycosylation changes within cells upon response to stimuli remains challenging because of the complexity of this large family of post-translational modifications (PTMs). We developed an original tool, enabling labeling and visualization of the cell cycle key-regulator β-catenin in its O-GlcNAcylated form, based on intramolecular Förster resonance energy transfer (FRET) technology in cells. We opted for a bioorthogonal chemical reporter strategy based on the dual-labeling of β-catenin with a green fluorescent protein (GFP) for protein sequence combined with a chemically-clicked imaging probe for PTM, resulting in a fast and easy to monitor qualitative FRET assay. We validated this technology by imaging the O-GlcNAcylation status of β-catenin in HeLa cells. The changes in O-GlcNAcylation of β-catenin were varied by perturbing global cellular O-GlcNAc levels with the inhibitors of O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). Finally, we provided a flowchart demonstrating how this technology is transposable to any kind of glycosylation.